The ethics toolkit a compendium of ethical concepts and methods - Baggini, Julian; Fosl, Peter S. (Hoboken, NJ Wiley-Blackwell, 2024)
The Ethics Toolkit offers an engaging and approachable introduction to the core concepts, principles, and methods of contemporary ethics. Explaining to students and general readers how to think critically about ethics and actually use philosophical concepts, this innovative volume provides the tools and knowledge required to engage intelligently in ethical study, deliberation, and debate. Invaluable as both a complete guide and a handy reference, this versatile resource provides clear and authoritative information on a diverse range of topics, from fundamental concepts and major ethical frameworks to contemporary critiques and ongoing debates. Throughout the text, Fosl and Baggini highlight the crucial role ethics plays in our lives, exploring autonomy, free will, consciousness, fairness, responsibility, consent, intersectionality, sex and gender, and much more.
Includes bibliographical references and index.
Keywords: Ethics